4(x+2)=3(x-3)

Simple and best practice solution for 4(x+2)=3(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=3(x-3) equation:


Simplifying
4(x + 2) = 3(x + -3)

Reorder the terms:
4(2 + x) = 3(x + -3)
(2 * 4 + x * 4) = 3(x + -3)
(8 + 4x) = 3(x + -3)

Reorder the terms:
8 + 4x = 3(-3 + x)
8 + 4x = (-3 * 3 + x * 3)
8 + 4x = (-9 + 3x)

Solving
8 + 4x = -9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8 + 4x + -3x = -9 + 3x + -3x

Combine like terms: 4x + -3x = 1x
8 + 1x = -9 + 3x + -3x

Combine like terms: 3x + -3x = 0
8 + 1x = -9 + 0
8 + 1x = -9

Add '-8' to each side of the equation.
8 + -8 + 1x = -9 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = -9 + -8
1x = -9 + -8

Combine like terms: -9 + -8 = -17
1x = -17

Divide each side by '1'.
x = -17

Simplifying
x = -17

See similar equations:

| 7-8x=131-36x | | 14-6x=74 | | 70*70= | | 7n-3=7n+12 | | x^3-8x^2-4x+32=0 | | 2m=42 | | 72-2x^2=0 | | 4y^2-8=2y^2 | | 23x-9-14x+3=23x-6-14x+16 | | 7x-(2x+4)=15 | | 2+3(x-8)=3-8(x-6) | | n^2+10n+20=-1 | | --8(t-5)-(t+4)=6 | | 2x-8y=3 | | 2n+20n+40=-2 | | 9x+3y=12 | | 18x-2x^3=0 | | 0.6k+44=0.48k+8 | | .33d+7=12-.66d | | x^3+3x^2-49x-147=0 | | -8(t-5)-(t+4)=6 | | 32x^2-16x=0 | | 10n-16=74 | | x+2=36 | | 33x^2+22x=0 | | 6k= | | 1,2x=4,8 | | 9k-12k+3k= | | 2xy+17xy= | | 12-48n^2=0 | | 2x=1/5 | | 15a^2-60a=0 |

Equations solver categories